A Standardised Algorithm for the Determination of Position Errors by the Example of GPS with and without ’Selective Availability’ - Harre, Ingo (The International Hydrographic Review, 2001)
Today, the accuracy of position determination ashore or at sea is no longer a technical problem, but mainly a problem of clear mathematical formulation. This paper deals with the determination of accuracy. The results of the study by Burt et al (1965), developed further by the author over the years, are taken as a basis for the discussion. This paper describes a complete algorithm which is made available in the World Wide Web. The algorithm is used to evaluate GPS measurements with and without Selective Availability and to show differences in accuracy.